Financial Performance and Tax Avoidance in Large and Small Firms - Pilar Aji Delphiano; Dahlifah Dahlifah (Research of Accounting and Governance, 2026)
This study analyzes the influence of liquidity, activity, profitability, and solvency on tax avoidance, with firm size as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. The study was motivated by inconsistent findings regarding the relationship between financial performance and tax avoidance, particularly in manufacturing companies with complex operations and significant tax exposure. A quantitative approach was employed using purposive sampling, with panel data obtained from companies’ annual financial reports. Data were analyzed using panel regression and moderation testing in EViews. The results indicate that liquidity, activity, profitability, and solvency each have a significant effect on tax avoidance. Firm size moderates the relationships between liquidity and profitability and tax avoidance, suggesting that larger companies adopt different tax management strategies and possess greater financial flexibility than smaller firms. However, firm size does not moderate the relationships between activity, solvency, and tax avoidance. These findings contribute to the tax compliance and corporate finance literature by highlighting the moderating role of firm size in corporate tax behavior. Practically, the results provide insights for regulators to develop governance-based tax supervision policies that improve transparency and sustainable tax compliance in the manufacturing sector.